$a_{n} = ar^{n - 1}$

where a= first term

common ratio = r

number of terms = n

first term = a = 1

∴ $a_{3} = 1 \times r^{3 - 1}$ ⇒ $a_{3} = r^{2}$

similarly, $a_{5} = 1 \times r^{5 - 1}$ ⇒ $a_{5} = r^{4}$

As $a_{3} +a_{5}$ = 90

$r^{2} + r^{4}$ = 90

$r^{4} + r^{2}$ - 90 = 0

Considering this as a quadratic equation so we will find the factors of it

$\left ( r^{2} \right )^{2} + 10 r^{2} -9 r^{2}$- 90 = 0

$r^{2}( r^{2}$ + 10) -9($r^{2}$ + 10) = 0

∴ ( $r^{2}$ + 10)( $r^{2}$ - 9)

∴ $r^{2}$ + 10 = 0 and $r^{2}$ - 9 = 0

$r^{2}$ = - 10 $r^{2}$ = 9

r =$\pm\sqrt{-10}$ r = $\pm$ 3

The common ratio never be imaginary(complex number)

∴ common ratio = r = $\pm$ 3

2) If the first and the nth terms of G.P. are 'a' and 'b' respectively. If 'p' is the product of the first and the nth term then prove that : $p^{2} = (ab)^{n}$

$a_{n} = ar^{n - 1}$

nth term = b

∴ b = $ar^{n - 1}$

∴ $r^{n - 1} = \frac{b}{a}$

∴ r =$\left ( \frac{b}{a} \right )^\frac{1}{n - 1}$ -----------(1)

Now, the product of n terms = p

∴ p = a $\times$ ar $\times ar^{2} \times$ ...a$r^{n - 1}$

= $a^{n}\times r^{1 + 2 + 3 + ...+(n -1)}$

= $a^{n}\times r^{\frac {n(n -1)}{2}}$

=$a^{n}\left ( \frac{b}{a} \right )^{\frac{n(n-1)}{2}\times \frac{1}{(n -1)}}$

= $a^{n}\left ( \frac{b}{a} \right )^\frac{n}{2}$

= $a^{n}\left ( \frac{b^\frac{n}{2}}{a^\frac{n}{2}} \right )$

p = $a^{\frac{n}{2}} . b^{\frac{n}{2}}$

∴ p = $\left ( ab \right )^{\frac{n}{2}}$

∴ $p^{2} = \left ( ab \right )^{n}$

3) If the $p^{th}, q^{th} and r^{th}$ terms of G.P. are 'a' , 'b' and 'c' respectively then prove that

$a^{q-r}. b^{r -p} . c^{p -q}$ = 1

$a_{n} = ar^{n - 1}$

n = p,q and r and first term = A and common ratio = R

∴ $a_{p} = AR^{p - 1}$ $a_{q} = AR^{q - 1}$

$a_{r} = AR^{r - 1}$

$p^{th}$ term = a , $q^{th}$ = b and $r^{th}$ = c

∴ a = $A R^{p - 1}$ b = $A R^{q - 1}$ c =$A R^{r - 1}$

We have , $a^{q-r}. b^{r -p} . c^{p -q}$

Substitute the values of a,b and c we get

L.H.S = $\left ( AR^{(p -1)} \right )^{(q-r)}.\left ( AR^{(q -1)} \right )^{(r-p)}.\left ( AR^{(r -1)} \right )^{(p-q)}$

= $A^{(q -r +r - p + p -q)}. R^{(p-1)(q-r) +(q -1)(r-p)+(r -1)(p-q)}$

= $ A^{0} . R^{(pq -pr -q + r + qr-pq - r + p +rp - rq - p +q)}$

= 1. $R^{0}$

= 1 ---------Proved

From solved sums on geometric progression to Home

GMAT

GRE

1st Grade

2nd Grade

3rd Grade

4th Grade

5th Grade

6th Grade

7th grade math

8th grade math

9th grade math

10th grade math

11th grade math

12th grade math

Precalculus

Worksheets

Chapter wise Test

MCQ's

Math Dictionary

Graph Dictionary

Multiplicative tables

Math Teasers

NTSE

Chinese Numbers

CBSE Sample Papers